Modus Operandi Kekerasan Seksual Terhadap Anak Melalui Media Sosial TikTok - Aldi Evi Permana; Chazizah Gusnita (Anomie, 2023)
This study looks at the patterns and types of sexual assault against minors on the social media platform Tiktok. This research method employs qualitative and descriptive approaches based on Rational Choice Theory. The researchers used five sources, including three perpetrators of child and sexual abuse and two police officers. The study's findings indicated why each of the criminals engaged in sexual harassment and child abuse on the social media site TikTok. The three perpetrators utilize TikTok because it is simple to use, and the victim is active on TikTok, which makes it easier to approach. The culprit can view many videos and victim profiles on the TikTok app. Because environmental factors and relationships that exist in the friendship of one of them that help to find the victim and perpetrator also like to see the porn video, and the mode of perpetration with the way to approach the victims first, then like the posts and frequently comment. The criminal approached the victim via TikTok messenger after sending a message to the victim. The culprit stole the victim's heart, after which the offenders frequently made sexual calls and remarks. The offender picking the child as a victim is because the perpetrator is very glad to relate to an age group of children since it is easy to offer confidence to want to do and obey the criminal's desire and may also be used in terms of the victim's age and finances.